Transformasi Ruang Belajar: Implementasi Pojok Baca oleh Mahasiswa Kampus Mengajar Batch 5 di SDN 4 Bringin - Zakariya, Muhammad; Zumrotun, Erna (Universitas Nusantara PGRI Kediri, 2024)
This research aims to describe the transformation process in understanding how a learning space can be converted into a reading corner at SDN 4 Bringin, identify the obstacles that arise during the implementation of the Reading Corner and find the right solution, and find out the positive impact produced by the existence of a reading corner for students and school environment. This type of research is descriptive qualitative with data collection techniques using interviews, questionnaires and documentation. The implementation of the Reading Corner by Batch 5 Teaching Campus students at SDN 4 Bringin through the planning, preparation, implementation and evaluation stages showed a significant positive impact. Despite facing obstacles such as limited funds, lack of enthusiasm among some students, and inadequate infrastructure, solutions such as book donations and team encouragement helped overcome these problems. The Reading Corner provides a conducive learning environment, increases students' interest in reading, and supports literacy activities at school. Positive responses from students and support from teachers indicate that this program has succeeded in providing great benefits at SDN 4 Bringin.